Evidence for Integration of Cognitive, Affective, and Autonomic Influences During the Experience of Acute Pain in Healthy Human Volunteers - Powers, Jocelyn M.; Ioachim, Gabriela; Stroman, Patrick W. (Frontiers in Neuroscience, 2022)
Our psychological state greatly influences our perception of sensations and pain, both external and visceral, and is expected to contribute to individual pain sensitivity as well as chronic pain conditions. This investigation sought to examine the integration of cognitive and emotional communication across brainstem regions involved in pain modulation by comparing data from previous functional MRI studies of affective modulation of pain. Data were included from previous studies of music analgesia (Music), mood modulation of pain (Mood), and individual differences in pain (ID), totaling 43 healthy women and 8 healthy men. The Music and Mood studies were combined into an affective modulation group consisting of runs with music and positive-valenced emotional images plus concurrent presentation of pain, and a control group of runs with no-music, and neutral-valenced images with concurrent presentation of pain. The ID group was used as an independent control. Ratings of pain intensity were collected for each run and were analyzed in relation to the functional data. Differences in functional connectivity were identified across conditions in relation to emotional, autonomic, and pain processing in periods before, during and after periods of noxious stimulation. These differences may help to explain healthy pain processes and the cognitive and emotional appraisal of predictable noxious stimuli, in support of the Fields’ Decision Hypothesis. This study provides a baseline for current and future investigation of expanded neural networks, particularly within higher limbic and cortical structures. The results obtained by combining data across studies with different methods of pain modulation provide further evidence of the neural signaling underlying the complex nature of pain.